Dr Macnamara 1861-1931. - Betts, Robin (Liverpool University Press, 1998)
This well-researched historical biography is the first on Dr T.J. Macnamara, the first ex-elementary teacher to win a government post. Colleague and close friend of Lloyd George, and praised by Winston Churchill, Macnamara was an educationist, journalist and Cabinet Minister. This study of his life and career makes a major contribution to educational history as well as to the history of the Liberal Party, the National Union of Teachers (NUT) and British political history generally. Fascinating details of Macnamara?s pre-Parliamentary career are provided and, alongside the biographical account.